2021
DOI: 10.3390/ijerph18073769
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Perceptual, Socio-Relational, and Affective Skills of Five-Year-Old Children Born Preterm and Full-Term According to Their Body Mass Index

Abstract: The main purpose of this study was to compare the psychomotor development of five-year-old children born preterm and full term. The comparison included physical-motor, perceptual-motor, and socio-relational and affective skills. As low weight is one of the variables that most influences the psychomotor development of premature infants, a secondary aim was to analyze these skills according to their current body mass index (BMI). A prospective simple ex-post facto study was conducted. The sample consisted of 672… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Often, these children also presented behavioral problems or other conduct disorders, and when submitted to psychomotor re-education programs with emphasis on body mastery, they significantly improved their performance [5]. Therefore, the main objective of PM is the prevention and treatment of problems to enhance in students, not only the motor aspects but all aspects of personality that interrelate, namely, the ones of intellectual, social and affective nature [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Often, these children also presented behavioral problems or other conduct disorders, and when submitted to psychomotor re-education programs with emphasis on body mastery, they significantly improved their performance [5]. Therefore, the main objective of PM is the prevention and treatment of problems to enhance in students, not only the motor aspects but all aspects of personality that interrelate, namely, the ones of intellectual, social and affective nature [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Lin et al [35] assessed the general development of premature children using the Bayley scale of child development at 2 and 5 years of age, and observed unfavorable changes in neurodevelopment from 2 to 5 years of age; more than 70% of children who at 2 years of age had normal or borderline development were borderline at 5 years of age. Gil-Madrona et al [36] studied five-year-old children born preterm and full term. They observed that prematurity may have influenced some areas of psychomotor development, such as body image, motor dissociation, visual-motor coordination, and social and emotional aspects.…”
Section: Discussionmentioning
confidence: 99%
“…This theory underscores the importance of considering long-term exposure to socioeconomic disadvantage and its cumulative effects on health, including motor skills (19). Previous reports that indicate extracurricular physical activities can influence motor skills and cognition and provide a potential modifiable factor for SCD (20,21). Higher ADI values have been associated with faster cognitive decline in older adults; however, the relationship between ADI and motor skill decline in older adults requires further investigation to develop targeted interventions (7,14).…”
Section: Introductionmentioning
confidence: 97%